Clinical hypoxemia score for outpatient child pneumonia care lacking pulse oximetry in Africa and South Asia - Schuh, Holly B.; Hooli, Shubhada; Ahmed, Salahuddin; King, Carina; Roy, Arunangshu D.; Lufesi, Norman; Islam, ASMD Ashraful; Mvalo, Tisungane; Chowdhury, Nabidul H.; Ginsburg, Amy Sarah; Colbourn, Tim; Checkley, William; et al. (Frontiers in Pediatrics, 2023)
Background: Pulse oximeters are not routinely available in outpatient clinics in low-and middle-income countries. We derived clinical scores to identify hypoxemic child pneumonia.Methods: This was a retrospective pooled analysis of two outpatient datasets of 3-35 month olds with World Health Organization (WHO)-defined pneumonia in Bangladesh and Malawi. We constructed, internally validated, and compared fit & discrimination of four models predicting SpO2<93% and <90%: (1) Integrated Management of Childhood Illness guidelines, (2) WHO-composite guidelines, (3) Independent variable least absolute shrinkage and selection operator (LASSO); (4) Composite variable LASSO.Results: 12,712 observations were included. The independent and composite LASSO models discriminated moderately (both C-statistic 0.77) between children with a SpO2<93% and >94%; model predictive capacities remained moderate after adjusting for potential overfitting (C-statistic 0.74 and 0.75). The IMCI and WHO-composite models had poorer discrimination (C-statistic 0.56 and 0.68) and identified 20.6% and 56.8% of SpO2<93% cases. The highest score stratum of the independent and composite LASSO models identified 46.7% and 49.0% of SpO2<93% cases. Both LASSO models had similar performance for a SpO2<90%.Conclusions: In the absence of pulse oximeters, both LASSO models better identified outpatient hypoxemic pneumonia cases than the WHO guidelines. Score external validation and implementation are needed.